Analysis of the 5 iron golf swing when hitting for maximum distance - Healy, A.; Moran, K. A.; Dickson, J.; Hurley, C.; Smeaton, A. F.; O'Connor, N. E.; Kelly, P.; Haahr, M.; Chockalingam, N. (Journal of Sports Sciences, 2011)
Most previous research on golf swing mechanics has focused on the driver club. The aim of this study was to identify the kinematic factors that contribute to greater hitting distance when using the 5 iron club. Three-dimensional marker coordinate data were collected (250 Hz) to calculate joint kinematics at eight key swing events, while a swing analyser measured club swing and ball launch characteristics. Thirty male participants were assigned to one of two groups, based on their ball launch speed (high: 52.9 ± 2.1 m/s; low: 39.9 ± 5.2 m/s). Statistical analyses were used to identify variables that differed significantly between the two groups. Results showed significant differences were evident between the two groups for club face impact point and a number of joint angles and angular velocities, with greater shoulder flexion and less left shoulder internal rotation in the backswing, greater extension angular velocity in both shoulders at early downswing, greater left shoulder adduction angular velocity at ball contact, greater hip joint movement and X Factor angle during the downswing, and greater left elbow extension early in the downswing appearing to contribute to greater hitting distance with the 5 iron club.